Beneficial Effects of Hypercapnic Acidosis on the Inhibition of Transforming Growth Factor β-1-induced Corneal Fibrosis in Vitro. (4th May 2021) - Chang, Yu-Min; Cian, An-An; Weng, Tzu-Heng; Liang, Chang-Min; Pao, Shu-I; Chen, Ying-Jen
ABSTRACT: Purpose: Corneal scarring is a common poor outcome of corneal trauma. Transforming growth factor β-1 plays a vital role in corneal fibrosis, inducing keratocyte transformation to myofibroblasts. Other than corneal transplantation, no other curative treatment methods for corneal scarring are currently available. Hypercapnic acidosis exerts anti-inflammatory and anti-migratory effects on numerous organs; however, its effect on corneal fibroblasts remains unknown. Hence, this study aimed to evaluate the effect of hypercapnic acidosis on transforming growth factor β-1-induced fibrosis in corneal fibroblasts and to elucidate the underlying mechanisms. Materials and Methods: Corneal fibroblasts were obtained from human limbal tissue and cultured with or without transforming growth factor β-1 under hypercapnic acidosis or no-hypercapnic acidosis conditions, and subjected to scratch wound, cell migration, and collagen matrix contraction assays. Furthermore, immunocytochemistry was performed to evaluate the alpha-smooth muscle actin stress fiber. Finally, western blotting was performed to assess the expression of proteins in the NF-κB and Smad pathways. Results: Hypercapnic acidosis suppressed collagen gel contraction capacity in transforming growth factor β-1-treated corneal fibroblasts and inhibited transforming growth factor β-1-induced cell migration. Moreover, hypercapnic acidosis downregulated corneal fibrosis marker alpha-smooth muscle actin in transforming growth factor β-1-treated corneal fibroblasts. Furthermore, hypercapnic acidosis suppressed transforming growth factor β-1-induced fibrosis, at least partly, by inhibiting Smad2/3 phosphorylation and down-regulating p -IκB-dependent and RelB signaling transduction. Conclusions: Hypercapnic acidosis inhibits transforming growth factor β-1-induced corneal fibroblast migration, collagen gel contraction capacity, and alpha smooth muscle actin expression, potentially through the Smad and NF-κB pathways. Therefore, hypercapnic acidosis may be a potentially useful anti-fibrotic therapy for corneal scarring.